Detrimental Effect of Alprazolam on Sperm Viability ofMice (Mus musculus) Exposed to Chronic Unpredictable Mild Stress - Intan Indah Permatasari; Reny I’tishom; HanikBadriyah Hidayati; Irwanto (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective: This study aims to investigate the effect of alprazolam administration on sperm viability of mice (Mus musculus) strain Balb/C following CUMSfor 53 days. Method: This study used a true experimental design through randomization. Control group kept undisturbed without treatment and therapy throughout 60 days. K1 and K2 were exposed to a 53 day period of CUMS along with 7-day pretreatment adaptation. K2 was adapted for a week, stressed for 53 days along with cotreatment of alprazolam (4 mg/kg BW). Results: K1 and K2 showed insignificant improvement of sperm viability (p > 0.05).Meanwhile, K0 and K1 showed significant value compared to K2 (p<0.05). K2 showed little increase of sperm viability in CUMS group along with subsequent treatment of alprazolam. Conclusion: Overall, the results indicate an insignificant effect of alprazolam on sperm viability of CUMS-induced mice.